Comparison And Analysis Of Physicochemical Properties Of Homemade Grape Juice And Commercial Juices Available In The Local Markets In Erbil City (International Journal of Environmental Sciences, 2025)
Grapes (Vitis vinifera L.) belong to the family Vitaceae that are the best source of energy. The objective of this study was to compare the physicochemical analysis and sensory evaluation of natural fresh grape juices and two branded grape juice. Three treatments were evaluated, consisting of combinations between natural fresh grape juice and two branded grape juice. Approximately one liter of juice was obtained per treatment. Analyses of moisture content, pH, titrable acidity and total soluble solids Brix. The physiochemical properties of moisture content, pH, titratable acidity and total soluble solid (TSS) showed diversity among genotype with range of 81.694 to 89.924 present, 3.60 to 4.64, 0.817 to 1.117 percent and 6.7 to 17.1 °Brix respectively. As well as, sensory evaluation was conducted. There was a significance difference (p<0.05) between the natural and branded grape juice samples in the appearance, aroma, colour, taste, texture and overall acceptability.